Complementary Resources and Cooperative Research: A Model of Research Joint Ventures Among Competitors - Sinha, Deepak K.; Cusumano, Michael A. (Management Science, 1991)
We present a model of research joint ventures in which if firms have highly complementary skills and resources then they prefer to cooperate in areas where the technology is highly appropriable, as in applied research. The model also indicates that large firms have a greater incentive to cooperate because they are better positioned to capture the benefits of a research venture. These findings seem to explain why cooperative research among rival firms in Japan has been applied rather than basic and conducted frequently among large companies. But firms prefer as small a partner as possible to limit the sharing of research results, creating a tension that may make cooperative efforts among rivals difficult to manage. For this reason, cooperation with organizations, such as universities or nonprofit institutions, may be a viable alternative for firms looking for complementary skills and resources.